The health care of the male population in times National Policy for Integral Attention to Men's Health: what they say - Maria Elizabete Rodrigues Viana Bete; Maria Elizabete Bete (Universidad de Alicante, 2015)
This study aimed to analyze the relationship of man with their health care. Even though there are advances in healthcare, many men have the idea that the Basic Health Units (BHU) services are intended for women, children and elderly. This was a qualitative study, an exploratory / descriptive, as subjects had 20 men enrolled in BHU, whose testimonies were collected through a semi-structured interview, and all recorded and transcribed for later analysis and interpretation . The results showed that the culture historically established that man is to be strong and that therefore any sign of illness or even a behavior with your health care demonstrates his vulnerability, only contributes to making ill-health; the everyday life of being male influence in weakening or removal of the men on questions of self-care and the search for health services; and that all men surveyed are unaware of the National Policy for Integral Attention to Men's Health. The study contributes to reflections about the Family Health Strategy forward to planning actions to improve the health care of the man.